SISTEM PENETAPAN GUBERNUR KEPALA DAERAH ISTIMEWA YOGYAKARTA DALAM SISTEM PEMILIHAN KEPALA DAERAH BERDASARKAN PASAL 18 AYAT (4) UUD 1945 - Widodo, Ismu Gunadi (Jurnal Dinamika Hukum, 2011)
The Yogyakarta Specialist Region, both historical and juridical have strong legitimacy as special regions. Historically, (1) privilege status of Yogyakarta is a conscious political choice taken by the ruler of Yogyakarta, namely Sultan HB IX and Paku Alam VIII, and not the granting of national political entity; (2) Yogyakarta provide space areas and concrete for the Indonesian population early. Third, Yogyakarta became the savior when Indonesian forces in crisis situations to preserve the Declaration of Independence August 17, 1945. While legally the First, the consistency at the level that recognizes the juridical existence of a region that is special. Second, the consistency of recognition of the status of a regional specialty is not followed by a comprehensive arrangement on the substance of the privilege of an area. Special of DIY also reflected in the mechanism of filling the vacancy Guvernor and the Deputy Governor, with the appointment/establishment of Sri Sultan and Sri Pakualam directly by the President. The constitutional system of decision Hamengkubuwono X and Sri Pakualam, as Governor and Deputy Governor of DIY is not contradictory with the Constitution (unconstitutional) for determining the gain legitimacy from the community (community wishes).  Keywords: specialty of DIY, governor determination system, regional head of electoral systems